RETRACTED: Natural Killer Cell-Derived Exosomal miR-3607-3p Inhibits Pancreatic Cancer Progression by Targeting IL-26 - Sun, Hongwei; Shi, Keqing; Qi, Kai; Kong, Hongru; Zhang, Jie; Dai, Shengjie; Ye, Wen; Deng, Tuo; He, Qiye; Zhou, Mengtao (Frontiers in Immunology, 2019)
Increasing evidences have suggested that natural killer (NK) cells in the tumor microenvironment are involved in the regulation of cancer development. However, the potential biological roles and regulatory mechanisms of NK cells in pancreatic cancer (PC) remain unclear. Co-culture system of NK cells with PC cells is used to test the ability of cancer cell proliferation, migration and invasion both in vitro and in vivo. And tail vein intravenous transfer was used to test metastasis in vivo. Meanwhile, extracellular vesicles (EVs) were separated and examined. Furthermore, reporter assay and Biotin-RNA pull down assay were performed to verify the interaction between molecules. NK cells can inhibit the malignant transformation of co-cultured PC cells both in vivo and in vitro, which requires miR-3607-3p. miR-3607-3p is found enriched in the EVs of NK cells and transmitted to PC cells, and low level of miR-3607-3p predicts poor prognosis in PC patients. It can also inhibit proliferation, migration and invasion of PC cells in vitro. Importantly, IL-26 is found to be a direct target of miR-3607-3p in PC cells. miR-3607-3p enriched in EVs derived from NK cells can inhibit the malignant transformation of PC probably through directly targeting of IL-26.